Faktor Yang Mempengaruhi Pemimpin Komsel Dalam Menjalankan 3P - Go Andreas Agus Setiawan; Stephanus Karnadhi (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Every Sunday, the church holds a sermon, but it’s only one-way. In order to ensure that God’s Word is applied by the congregation, community life within the church is the most effective way. In a cell community there is a 3P process (Shepherding, Discipleship, and Outreach). A cell group leader who has a Shepherd’s Heart is a very influential key to the success of 3P. By forming a core team within the group, new potential leaders will emerge in the cell community, so the discipleship process can be said to be successful. There is no “one man show” in a healthy cell community. In this case, the intrinsic factor of a leader (having a personal relationship with God) plays a major role in the successful growth of cell community members. It cannot be denied that God gives growth (Corinthians 3:6-8). 3P is also influence by extrinsic factors (the relationship between the leaders and members), where a leader is expected to be a mentor who provides exemplary with the goal of bringing members into a right relatonship with God, building to full maturity in Christ, so that they can multiply the whole process in others as well.